Soluble Vascular Adhesion Protein 1 (sVAP-1) as a biomarker for pregnancy complications: A pilot study. - Marianna Danielli; Roisin C Thomas; Clare L Gillies; David G Lambert; Kamlesh Khunti; Bee Kang Tan (PLoS ONE, 2023)
Background Vascular adhesion protein 1 (VAP-1) has been implicated in a wide range of clinical conditions. Moreover, serum levels are associated with disease prediction and progression in several clinical studies. There is a paucity of data on VAP-1 and pregnancy. Given the emerging role of VAP-1 in pregnancy, the aim of this study was to examine sVAP-1 as an early biomarker of pregnancy complications, especially hypertension during pregnancy. The objectives of the study are to associate sVAP-1 levels with other pregnancy complications, patient demographics and blood tests performed throughout pregnancy. Methods We conducted a pilot study in a cohort of pregnant women (gestational week lower than 20 at the time of recruitment) attending their first antenatal ultrasound scan at the Leicester Royal Infirmary (LRI, UK). Data were both prospectively generated (from blood sample analysis) and retrospectively collected (from hospital records). Results From July and October 2021, a total of 91 participants were enrolled. Using ELISA (enzyme-linked immunosorbent assay), we found reduced serum levels of sVAP-1 in pregnant women with either pregnancy induced hypertension (PIH) (310 ng/mL) or GDM (366.73 ng/mL) as compared to controls (427.44 ng/mL and 428.34 ng/mL, respectively). No significant difference was found between women with FGR compared to controls (424.32 ng/mL vs 424.52 ng/mL), and patients with any pregnancy complications compared to healthy pregnancies (421.28 ng/mL vs 428.34 ng/mL). Conclusion Further studies are needed to establish whether or not sVAP-1 might be considered as an early, non-invasive, and affordable biomarker to screen women who will develop PIH or GDM. Our data will aid sample size calculations for such larger studies.